PROMIS Physical Function Score Strongly Correlates With Legacy Outcome Measures in Minimally Invasive Lumbar Microdiscectomy. Issue 6 (15th March 2019) - Khechen, Benjamin; Haws, Brittany E.; Patel, Dil V.; Bawa, Mundeep S.; Elboghdady, Islam M.; Lamoutte, Eric H.; Karmarkar, Sailee S.; Singh, Kern
Abstract : Study Design: Retrospective cohort. Objective: This study aims to determine the validity of the patient-reported outcomes measurement information system (PROMIS) physical function (PF) in minimally invasive lumbar discectomy (MIS LD) patients. Summary of Background Data: PROMIS was designed to allow for assessment of clinical outcomes in fewer questions than previous outcome measures with the goal of reducing noncompliance associated with longer, time-consuming surveys. However, there exists a paucity of evidence regarding the efficacy of the PROMIS PF domain in patients undergoing MIS LD. Methods: A surgical database of patients undergoing 1–3 level MIS LD was retrospectively reviewed. Postoperative changes in PROMIS PF scores were analyzed at 6-weeks, 12-weeks, and 6-months using paired Student t tests. PROMIS scores were compared to Oswestry disability index (ODI), visual analog scale (VAS) back, and VAS leg scores. Correlations were tested using Pearson correlation coefficient. Results: Forty-one MIS LD patients were identified, reporting an average preoperative PROMIS PF score of 35.36 ± 7. Patients demonstrated significant improvement in ODI, VAS back, and VAS leg scores. Additionally, strong associations with PROMIS scores were observed for preoperative and postoperative ODI (r range: 0.5735–0.8543) and postoperative VAS back (r range: 0.5332–0.6522) and VAS leg pain (r range: 0.5257–0.6412). Conclusion: Patients undergoing MIS LD demonstrated significant improvements in PROMIS PF, ODI, VAS back, and VAS leg pain postoperatively. Additionally, improvements in PROMIS physical function scores at each postoperative time point were determined to be significantly correlated with ODI, VAS back, and VAS leg pain. The results of the current study demonstrate PROMIS PF has strong utility as a postoperative outcome assessment tool. Level of Evidence: 4 Abstract : This study evaluates the validity of patient-reported outcomes measurement information system (PROMIS) physical function (PF) in patients undergoing minimally invasive lumbar microdiscectomy. Our findings demonstrate that PROMIS PF has utility as a postoperative assessment tool and can offer patients convenience by minimizing the time required for survey completion.